Waste Policy Formulation and Implementation: Recycling and Landfill - Greaves, Christopher (Cranfield University, 1994)
This thesis considers recycling as one option to improve the environmental performance of industry in the UK. A systems approach is used to identify objectives and capabilities of legislative and industrial agencies and to analyse issues in the broad context of waste policy formulation and implementation which spans both constituencies. It is shown that regulatory change to empower industrialists as decision takers is limited by a shortage of recycling infrastructure in the UK. Although well resourced firms are developing progressive waste policies in house, other firms are less well equipped to respond to regulatory pressures in a manner that is congruent with legislative objectives. An innovative option to develop recycling facilities for construction wastes at a landfill site is assessed, considering the roles of construction firms, skip hauliers and waste managers. An investigation is conducted into the practices employed by construction firms that influence wastes arising and likely changes to such practices. It is shown that pressures on construction firms are leading to some improvements to waste streaming that favour the recycling option. A spatial model of landfill catchment is used to estimate the elasticity of the volume of a given waste type delivered to a landfill site with respect to prices charged at the site and competing facilities. The option to recycle a substantial fraction of construction waste is compared with the null option of continuing to landfill waste without pre-treatment using a comparative cost benefit model. This model shows that, in the case of construction waste, benefits due to extending the working life of a landfill pit can be more significant than revenue effects for waste managers. Whether these benefits justify the costs of recycling is shown to be dependent on characteristics of particular landfill sites and